CONNECTION BETWEEN EPILEPSY AND AUTISM SPECTRUM DISORDER - N. N. Maslova; V. A. Skorobogatova; N. V. Yur’eva; N. E. Maslov (Эпилепсия и пароксизмальные состояния)
The role of epilepsy in developing autism spectrum disorders (ASD) is not well understood. According to some reports, epilepsy of early childhood is often found in patients with autism of early childhood. In such children, epilepsy can progress at later periods, while the presence of both disorders in one child has a specific clinical pattern and requires specific treatment. The question whether suppression of epileptic discharges on the EEG could lead to cognitive improvement in children with ASD remains open. Likewise, the etiology of autism and its possible links to epilepsy and other pediatric disorders need more research. Here we present an overview of recent clinical studies on the proposed connection between epilepsy and ASD.